Exploring an antioxidant and hemostasis activity of peptides from Antarctic krill Euphausia superba - Raksha, Nataliia; Halenova, Tetiana; Vovk, Tetiana; Savchuk, Olexiy; Beregova, Tetyana; Ostapchenko, Lyudmila (Ukrainian Antarctic Journal, 2024)
The goal of the study was to obtain the fractions of endogenous and hydrolytic peptides from the hydrobiont Euphausia superba and evaluate their antioxidant potential and possible activity against certain hemostasis factors. The fraction of endogenous peptides was isolated by stepwise precipitation of proteins with perchloric acid and ethanol. Peptides with a molecular weight up to 5 kDa were isolated by by ultrafiltration. Hydrolysis with trypsin was used to obtain hydrolytic peptides. The purity of peptide fractions was confirmed by SDS-polyacrylamide gel electrophoresis. Antioxidant activity was assessed by analyzing the peptides’ reducing power, 2,2-diphenyl-1-picrylhydrazyl, and nitric oxide radical scavenging activity. To assess the effect of peptides on the amidolytic activity of thrombin, active thrombin was preincubated with peptide fractions, and further thrombin activity was determined using the chromogenic substrate S2238. The ability of the peptides to influence ADP-induced platelet aggregation was tested in platelet-rich plasma. The results showed that endogenous and hydrolytic peptides exhibit moderate antioxidant activity; however, endogenous peptides were more potent antioxidants than peptides produced by trypsin hydrolysis. The influence of E. superba peptides on some hemostasis factors has been established. Inhibition of ADP-induced platelet aggregation by hydrolytic peptides (by 1.76 times) was found, while endogenous peptides possess the opposite effect. The differences in the activity and effectiveness of the peptides indicate that the fractions contain molecules that differ in amino acid composition. Considering the data, E. superba can be a source for peptides with moderate antioxidant activity and peptides that can affect the activity of key hemostasis factors.